SCIENTOMETRIC ANALYSIS AND TITLES WORD LINKAGE IN DOCTORAL THESIS OF VEGETABLE PATHOLOGY DURING THE PERIOD OF 2007-2019 - V, Amaravathi (International Journal of Research -GRANTHAALAYAH, 2024)
There 2,327 citations were identified from 12 doctoral theses the highest 5(41.67%) number of theses submitted in 2009. Out of 2,327 Citations there are 1,408(60.50%) citations from “Journal Articles”, 400(17.19%) are from “Books”, 317(13.63%) are from “Conference proceedings”, 172(7.40%) are from “Thesis and Dissertations”, 236(16.76%) were “j.of.Phytopatholohy” from “United Kingdom”, is published 78(2.84%) were from “Indian j.mycol.pl.Pathol” Published from “India”. 14(14.15%) from “USA” is the second top country, 412(29.27%) were highest from the period “2008-1998”, 391(27.77%) references from the period “1997-1987”.